The Ghost of Trials Past: Transitional Justice in Greece, 1974–1975. (May 2022) - Hatzivassiliou, Evanthis
Abstract : There were major guidelines in the application of Greek transitional justice in 1974–5. Trials connected with politics had often taken place in Greece: in 1922, 1935 and during the civil war in the 1940s. Justice had often been instrumentalised during previous internal conflicts, mortgaging both the interwar republic and the post-war democracy. The 1974–5 transition followed a different path. According to the internal documents of the Greek government, there was constant care to uphold the rule of law and conform to the emerging international standards concerning human rights. This was seen as a necessary precondition for the establishment of a modern European democracy.